Quantitative estimation of AgNORs in inflammatory gingival overgrowth in pediatric patients and its correlation with the dental plaque status - Mukhopadhyay S (Wolters Kluwer Medknow Publications, 2009)
Background and Objectives: Nucleolar organizer Regions (NORs) are situated within the nucleolus of a cell. The proteins are selectively stained by the silver colloid technique that is known as the AgNOR technique. AgNOR stain can be visualized as a black dot under the optical microscope. The present study aimed to evaluate the cases for quantitative estimation of AgNORs in the epithelial cells in various grades of gingival overgrowth to that of normal gingival tissues. Materials and Methods: Only preadolescent and adolescent groups aged up to 14 years were selected. Twenty normal and 31 disease cases of gingival overgrowth were selected. The tissue sections were stained by the hematoxylin and eosin (HandE) technique for the routine histological evaluation, while the AgNOR counts were performed through the improved one-step method of Ploton et al. Results: HandE staining revealed five different types of gingival overgrowth. The plaque index (PI), gingival index (GI), and AgNOR count were not significantly (P> 0.05) higher than that of control cases in pyogenic granuloma, puberty gingivitis, and in drug-induced gingival overgrowth cases. In gingival fibromatosis cases, for comparison of different indices t-tests were done. The PI when compared with AgNOR count was found significant at 5% level and 0.1% level for mixed and permanent dentition, respectively. The GI when compared with AgNOR count was found significant at 1% level and 0.1% level in mixed and permanent dentitions, respectively.